Relation-making, time, and critique - Kramer, Max; Schaflechner, Jürgen (Dastavezi, 2020)
With Dastavezi we link writings in Cultural Anthropology, South Asian Studies, and Critical Theory with audio-visual compositions and independent film. Establishing such connections takes time. Dastavezi provides a platform for slow- paced and multi-mediated research in the social sciences to propagate novel, alternative, and critical views on and from South Asia. With the help of the contributions to each issue (audio-visual and written), we reflect on the potentialities and challenges emerging from linking textual and audio-visual formats in social science research. We will continue to use the journal’s introduction as a way to theorize the notion that critical research does not emerge through written discourse alone but results from aesthetic and affective processes that are present in it and intertwined with it.